Digital tracking of girls exposed to community led alternative rites of passage to prevent female genital mutilation/cutting, and child, early and forced marriages in Kenya: a longitudinal study - Kawai, David; Mbogo, Bernard; Opanga, Yvonne; Muhula, Samuel; Esho, Tammary C.; Conradi, Hilke; Rutto, Viola J.; Lugayo, Denge; Matanda, Dennis J. (Frontiers in Reproductive Health, 2025)
IntroductionFemale genital mutilation/cutting (FGM/C) and child marriage (CEFM) are harmful practices that are a human rights violation. For decades, many interventions have been implemented to end these practices. One such intervention is the Alternative Rite of Passage (ARP), which allows girls to go through a meaningful rite of passage without the cut. The ARPs have come under scrutiny due to a lack of data to show how effective ARPs have been. This study aimed to establish the effect of the Community-Led Alternative Rite of Passage (CL-ARP) model on incidences of FGM/C, CEFM and keeping girls and young women in school.MethodsThe study adopted a longitudinal design where girls and young women were enrolled into the CL-ARP programme and later followed up for over three years to assess the effectiveness of the CL-ARP model in preventing incidences of FGM/C, CEFM and keeping girls in school. A total of 2,647 girls aged 10–23 years who resided in Kajiado County were recruited and followed up post-exposure to CL-ARP. Data analysis involved conducting descriptive and logistic regression analyses.ResultsThe CL-ARP programme kept 98% of girls free of FGM/C, 99% free of CEFM and 98% kept in school. 41 cases of FGM/C, 12 cases of CEFM and 48 cases of school dropouts were reported three years post-exposure. Girls who underwent FGM/C had been kept free of FGM/C for an average of 39.5 months, those who experienced CEFM had been kept free of CEFM for an average of 40.2 months, and those who dropped out of school had been kept in school for an average of 38.5 months. Girls and young women who experienced instances of threats/violence were more likely to experience FGM/C, CEFM and drop out of school than those who had not.ConclusionsThe CL-ARP programme was successful in keeping the majority of girls and young women free of FGM/C and CEFM, and retained in school post-enrollment. Reported cases of FGM/C, CEFM and school dropouts underline the importance of considering other contextual factors such as gender-based violence that may continue to put girls and young women at risk despite embracing CL-ARP.